Binding of metallic ions to the outer membrane of Escherichia coli. - Hoyle, B (1983)
The binding of metal ions by the outer membrane of Escherichia coli K-12 strain AB264 was investigated by using outer membrane obtained after Triton X-100 extraction of purified cell envelopes. Binding studies, conducted under saturating conditions, indicated a selective trapping of certain metallic ions. Low-dose electron microscopy of metal-loaded samples revealed an aggregative deposition of lead on one surface of the membrane which suggests that at least one distinctive binding site is asymmetrically arranged in these outer membrane vesicles.